Organizational culture, work–life balance, and reward systems as determinants of employee retention in a construction company in Malaysia - Edward, Eric Jefrey; Abas, Bahijah; Abdul Rohman, Nazirah (International Journal of Accounting, Finance and Business, 2025)
This conceptual paper examines how organizational culture, work–life balance, and reward systems function as key determinants of employee retention within Malaysia’s construction industry. Drawing exclusively from the theoretical perspectives outlined in this study, including the Conservation of Resources Theory, Social Exchange Theory, the Job Demands–Resources Model, and Herzberg’s Two-Factor Theory, the paper integrates organizational and personal factors to explain why employees choose to remain in high-risk, project-based environments. The arguments developed highlight that a supportive culture fosters belonging and psychological safety, balanced work–life conditions reduce strain and burnout, and an appropriate blend of intrinsic and extrinsic rewards sustains motivation and commitment. Based on this synthesis, the paper advances three hypotheses proposing that these determinants positively influence employee retention. By consolidating existing literature within a construction-specific context, this study provides a structured foundation for future empirical testing and contributes conceptually to understanding workforce stability in the construction sector.